2016
DOI: 10.18632/oncotarget.11889
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of KPNA2 is associated with a poor prognosis and contributes to OCT4 nuclear transportation in bladder cancer

Abstract: Recent studies show that Karyopherin alpha 2 (KPNA2) is up-regulated in quite a number of cancers and associated with poor prognosis. Here, we found that expression levels of KPNA2 and OCT4 are up-regulated in bladder cancer tissues and significantly associated with primary tumor stage and bladder cancer patients' poorer prognosis. Our data also showed decreased cell proliferation and migration rates of bladder cancer cell lines when the expression of KPNA2 and OCT4 was silenced. Meanwhile, cell apoptosis rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…Several studies have recently demonstrated that KPNA2 is up-regulated in multiple malignancies [23][24][25]. Its aberrant expression is often associated with adverse outcomes in affected patients, indicating that KPNA2 plays a signi cant role in carcinogenesis and tumor progression [23,26,27]. These ndings are supported by previous studies, which reported that KPNA2 may have a functional role in the malignant transformation of cells.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Several studies have recently demonstrated that KPNA2 is up-regulated in multiple malignancies [23][24][25]. Its aberrant expression is often associated with adverse outcomes in affected patients, indicating that KPNA2 plays a signi cant role in carcinogenesis and tumor progression [23,26,27]. These ndings are supported by previous studies, which reported that KPNA2 may have a functional role in the malignant transformation of cells.…”
Section: Discussionsupporting
confidence: 70%
“…Given its function in nucleocytoplasmic transport, KPNA2 mediates the translocation of various proteins and is involved in numerous cellular processes, such as cellular differentiation, proliferation and apoptosis, transcriptional regulation, immune response, and viral infection. Several studies have recently demonstrated that KPNA2 is up-regulated in multiple malignancies [23][24][25]. Its aberrant expression is often associated with adverse outcomes in affected patients, indicating that KPNA2 plays a signi cant role in carcinogenesis and tumor progression [23,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…KPNA2 is overexpressed in BCa and associated with poor prognosis [83]. Moreover, the expression levels of KPNA2 and OCT4 are significantly associated with primary tumor stage [84].…”
Section: The Hub Genes Potentially Associated With the Clinical Prognmentioning
confidence: 99%
“…A total of 3222 articles were retrieved from the database via the search strategy. Following the above inclusion and exclusion criteria, 36 articles [ 14 , 15 , 17 , 18 , 22 25 , 29 55 ] were enrolled in this meta-analysis (Fig. 1 ) and had 5198 cancer patients from China, Korea, Slovenia, Iran, Denmark, and Japan, who had been diagnosed with all types of solid tumors involving hepatocellular carcinoma (HCC), gastric cancer (GC), OSCC, esophageal squamous cell carcinoma (ESCC), cervical cancer, TSCC, breast carcinoma, colorectal carcinoma, gallbladder carcinoma, lung carcinoma, bladder carcinoma, anaplastic astrocytoma, prostate cancer, renal cell carcinoma, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 , 12 ] Further, the study inferred Oct4-positive cancer cells likely represent CSCs. [ 11 , 12 ] Other investigations have revealed that Oct4 is expressed abnormally in solid cancers, such as cervical carcinoma, [ 13 ] gastric carcinoma, [ 14 ] bladder carcinoma [ 15 ] among others.…”
Section: Introductionmentioning
confidence: 99%